Specifying OCL Constraints on Process Instantiations - Killisperger, Peter; Stumptner, Markus; Peters, Georg; Stückl, Thomas (Electronic Communications of the EASST, 2010)
Due to the variety of concerns affecting software development in large organisations, processes have to be adapted to project specific needs to be effectively applicable in individual projects. We describe a project aiming to provide tool support for this individualised instantiation of reference processes, based on an OCL-based specification of instantiation operations. The aim is not only to execute instantiation decisions made by humans but to automatically ensure correctness of the resulting process, potentially resulting in followup actions being executed or suggested.